2011
DOI: 10.1074/jbc.m110.177089
|View full text |Cite
|
Sign up to set email alerts
|

Modulating μ-Opioid Receptor Phosphorylation Switches Agonist-dependent Signaling as Reflected in PKCϵ Activation and Dendritic Spine Stability

Abstract: Thr 370 and Ser 375 to Ala) enabled etorphine, fentanyl, and DAMGO to use the PKC⑀ pathway. This was not due to the decreased recruitment of ␤-arrestin2 to the receptor signaling complex, because these agonists were unable to use the PKC⑀ pathway when ␤-arrestin2 was absent. In addition, overexpressing G protein-coupled receptor kinase 2 (GRK2) decreased the ability of morphine to activate PKC⑀, whereas overexpressing dominant-negative GRK2 enabled etorphine, fentanyl, and DAMGO to activate PKC⑀. Furthermore,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
57
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(64 citation statements)
references
References 41 publications
6
57
1
Order By: Relevance
“…When compared with other mu agonists, morphine induces less internalization of the mu opioid receptor (Borgland et al, 2003;McPherson et al, 2010;Zheng et al, 2011). This suggests that the prototypical role of b-arrestin 2 in initiating receptor internalization does not explain how the effects of morphine, but not of other mu agonists, are altered in mice lacking b-arrestin 2.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…When compared with other mu agonists, morphine induces less internalization of the mu opioid receptor (Borgland et al, 2003;McPherson et al, 2010;Zheng et al, 2011). This suggests that the prototypical role of b-arrestin 2 in initiating receptor internalization does not explain how the effects of morphine, but not of other mu agonists, are altered in mice lacking b-arrestin 2.…”
Section: Discussionmentioning
confidence: 64%
“…Compared with other mu agonists such as fentanyl, the relative inability of morphine to cause significant receptor phosphorylation, results in the recruitment of PKC to morphine, but not fentanyl, bound mu receptors (Zheng et al, 2011). As PKC is known to both scaffold with and phosphorylate JNK (Lopez-Bergami et al, 2005;Ping, 2003;Pontrelli et al, 2004), we propose that in wild-type mice, morphine recruitment of PKC activates JNK but that barrestin 2 recruitment limits further JNK activation.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Differential phosphorylation, tissue-, cell-, or agonist-dependent, has recently been postulated to create a "phosphorylation bar code" that offers a way to regulate signaling and trafficking of GPCRs (52). Such a mechanism could explain, for example, the differences in MOP receptor desensitization and trafficking induced by morphine versus DAMGO (5,38,49,50,54) or could determine the signaling pathway (PKC⑀ versus ␤-arrestin2) by which MOP agonists activate ERK (55). Cross-or transphosphorylation between receptors offers an additional level of complexity to the regulation of GPCR activity and trafficking (56) that could be involved in the functional inhibition of MOP receptors by NPFF receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that the change in the MOR binding affinity is not likely to be the mechanism for the fentanyldependent attenuation of MOR activation in oxaliplatininduced neuropathy. The second possibility for decreased G protein activation by fentanyl is upregulation of G protein-coupled receptor kinases (GRKs) because upregulation of the expression of GRKs might reduce opioid-stimulated G protein activation in animal pain models (34), and fentanyl showed a stronger interaction with the arrestin-GRK pathway compared with morphine (35,36). Therefore, we examined the expression level of GRK2, a major link to MOR, in the mTH in the oxaliplatin group by western blotting.…”
Section: Discussionmentioning
confidence: 99%